The implementation of management accounting practice and its relationship with performance in Small and Medium Enterprises sector - Ahmad, Kamilah (International Review of Management and Marketing, 2017)
There is scarce research into management accounting practices (MAPs) in small and medium-sized enterprises (SMEs) in the current literature. This study aims to explore the implementation of MAPs in SMEs and the relationship between MAPs implementation and performance. A questionnaire survey was conducted among Malaysian SMEs which yields 160 usable responses. The study demonstrates that the level of adoption of MAPs differs from traditional to more sophisticated approach. Costing system and performance measurement system appear to be a common MAPs used in SMEs regardless of the firms' size. Therefore the results suggest that the sophisticated MAPs are expected to be utilized by larger enterprise which is in line with the theoretical arguments of the effect of size in the adoption of MAPs. The findings also show that certain MAPs have significant relationships with performance. This study provides additional empirical evidences on the implementation of MAPs in SMEs and their relationships with performance.